2019
DOI: 10.18203/2394-6040.ijcmph20190483
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of breast cancer and estimation of its predicted future risk among females of urban slums of or above 35 years of age: a cross sectional study

Abstract: Background: Early detection and identification of the risk factors is crucial in minimizing morbidity and mortality arising due to breast cancer. Research has proven that, physiotherapist as a part of multidisciplinary team, plays an important role in treating these patients after surgery. However, evidence suggesting the role of physiotherapist in the domain of health promotion and prevention is limited. Thus an effort is made in this study to explore the level of awareness about the risk factors and preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…18 In a cross-sectional study among slum women above 35 years in Mumbai by Aurangabadkar SK et al in 2019 reported a higher proportion (12.5%) of participants had family history of breast cancer and 4% participants had underwent breast biopsy for history of benign breast disease. 19 In comparison the prevalence of family history of breast cancer and a history of previous biopsy due to benign breast disease in this study is lower. This may be attributed to the difference in geographical location and difference socio-cultural factors.…”
Section: Samplingcontrasting
confidence: 55%
See 1 more Smart Citation
“…18 In a cross-sectional study among slum women above 35 years in Mumbai by Aurangabadkar SK et al in 2019 reported a higher proportion (12.5%) of participants had family history of breast cancer and 4% participants had underwent breast biopsy for history of benign breast disease. 19 In comparison the prevalence of family history of breast cancer and a history of previous biopsy due to benign breast disease in this study is lower. This may be attributed to the difference in geographical location and difference socio-cultural factors.…”
Section: Samplingcontrasting
confidence: 55%
“…The study reported 8% women to be nulliparous, 5.5% participants gave birth after the age of 30. 19 Lower prevalence of nulliparous women and women giving birth after age of 30 in this study might be because this study is conducted in the urban slums and therefore the participants get married at an early age and also give birth at an early age of life.…”
Section: Samplingmentioning
confidence: 80%
“…The global burden of Breast cancer is expected to cross 2 million by the year 2030, with growing proportions from developing countries. Although age-standardized incidence rates in India are lower than in the United Kingdom (UK) of 25.8 versus 95 per 100,000, mortality rates are nearly as high as 12.7 versus 17.1 per 100,000, respectively as those of the UK [6] . Breast cancer incidence rates within India display a 3-4 fold variation across the country, with the highest rates observed in the Northeast and in major metropolitan cities such as Mumbai and New Delhi [6] .…”
Section: Introductionmentioning
confidence: 96%
“…Although age-standardized incidence rates in India are lower than in the United Kingdom (UK) of 25.8 versus 95 per 100,000, mortality rates are nearly as high as 12.7 versus 17.1 per 100,000, respectively as those of the UK [6] . Breast cancer incidence rates within India display a 3-4 fold variation across the country, with the highest rates observed in the Northeast and in major metropolitan cities such as Mumbai and New Delhi [6] . An educational interventional study found that there was about 25.71% of improvement of knowledge on Breast cancer and Breast Self-Examination (BSE) among school teachers, it was proved that Educational Interventional Program was effective, and also there is a need for a brief knowledge among school teachers regarding breast cancer [7] .…”
Section: Introductionmentioning
confidence: 96%